(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The current research seek to known the strategic planning for the taxes and its important , and its effect upon the investment , and this research was be in the general board of taxes, and the economical directorate of the ministry of finance , therefore this research started from the problem below: What level of the important and type of the research changeable of the research ( the strategic planning for the taxes and investment) in the research organization ? Is there any relation of the join and effect of the changeable of the research (the strategic planning for the taxes and investment)in the research organization ? Therefore this research depended a hypothetical sample that express about logic relation between the research changeable. The strategic planning for the taxes was considered explanatory changeable that has effect for the investment , because it was considered as receiving changeable. The head aim of this research is confirmation the important of depending of the strategic planning at the taxes fields to aiming the investment , as well as the knowledge of the effect of the strategic planning for the taxes upon the form and type of the investment when aim it. The research conclusion:- The moral effect appeared with the statistics purport for the strategic planning of the taxes and investment. The reduce of the relative important for the taxes as generality for the government ,because its activities was reduce to executing this aims that fixing the incomes to execute it , sociality the financial aim , because its share is 2% from the public balance of the government , as well as another aims such as society , economical ,and political aims. The increase of the taxes imports as a formal increase , resulting from the increase in the government expenses in addition to the inflation. This research was included the important recommendations:- Putting the important of all type of the investment at first interest for the maker the strategic planning of the taxes. Making full and activity strategic planning to sharing for executing of this aims. Putting strategic planning , including the aspirant aims to sharing with the developing of taxes in addition to incentive of investment.